Relation between QRS amplitude and left ventricular mass in the initial stage of exercise-induced left ventricular hypertrophy in rats - Bachárová, Ljuba; Michalak, Karol; Kyselovič, Ján; Klimas, Ján (Clinical and experimental hypertension, 2005)
International Laser Center, Bratislava, Slovak Republic. bacharvo@ilc.skThe aim of the study was to analyze the relationship between QRS amplitude and left ventricular mass (LVM) in early stages of two different experimental models of left ventricular hypertrophy (LVH) in rats: in exercise-induced hypertrophy and pathological hypertrophy due to genetically conditioned pressure overload. Three groups of experimental animals were studied: healthy control Wistar-Kyoto rats (WKYs), spontaneously hypertensive rats (SHRs), and WKY rats exposed to training by intermittent swimming (SWIM). Orthogonal electrocardiograms were recorded in each group at the age of 12 and 20 weeks, and the maximum spatial QRS vector (QRSmax) was calculated. Then the animals were sacrificed and LVM was measured. The specific potential of myocardium (SP) was calculated as a ratio of QRSmax to LVM. The QRSmax values did not follow the changes in LVM. At the end of the follow-up period, the highest values of QRSmax were recorded in the control WKY rats (0.80 +/- 0.05 mV). The QRSmax values in both groups with experimental LVH were significantly lower as compared with control animals (SHR 0.44 +/- 0.02 mV, p < 0.001; SWIM 0.53 +/- 0.04 mV, p < 0.001). Similarly, the SP values were significantly lower in both groups with experimental LVH as compared with control animals (SHR 0.42 +/- 0.02 mV/g, p < 0.001; SWIM 0.55 +/- 0.05 mV/g, p < 0.001). A decrease in QRSmax and SP was observed in both models of experimental LVH. We attributed these findings to the changes in electrogenetic properties of myocardium in the early stage of developing LVH. In other words, it is changes of nonspatial determinants that influence the resultant QRS voltage in terms of the solid angle theory.
Keywords: srdeční komory; hypertrofie levé komory srdeční; Hypertrophy, Left Ventricular; Electrocardiography; financování vládou; Evaluation Studies as Topic; krysa rodu Rattus; Heart Ventricles; Physical Conditioning, Animal; mužské pohlaví; Male; Rats; Organ Size; velikost orgánu; Financing, Government; elektrokardiografie; hodnotící studie jako téma; kondiční příprava zvířat